Characterizations of BMO f ( w ) - Harboure, Eleonor Ofelia (2004)
Abstract. In this paper we give two characterizations of func-tions with weighted mean oscillation over cubes controlled by anon-negative function ´, that is functions in BMO´(w). The ¯rstone, by conditions on their rearrangements, and the second one,by means of Riesz transforms and ´-Lipschitz functions. Theseresults extend those contained in [S] and [J].